270. X-ray acquisition of extremities: Image quality and dose optimization. (December 2018) - Angelini, L.; Pogliani, M.; Santucci, G.; Sanniti, S.; Cavagna, E.; Baldazzi, G.
Abstract : Purpose: In this study we changed acquisition parameters in X-ray acquisition of extremities (kV, mA, s and focal spot) trying to improve high and contrast resolution. The new technique (T2) was compared to a technique (T1) presenting the default parameter set by the manufacturer. The comparison regarded a dosimetric and a qualitative assessment[1] . Methods: For dose evaluation we calculated the entrance surface air Kerma (no backscatter) for each examination. For qualitative analysis of the clinical image, five radiologists examined two sets of X-ray images of patients of the same size, age and gender, showing: knee, ankle, foot, elbow, wrist and hand, the first of each set taken using T1 and comparing it with T2, confirming which image had the best quality. We used the TO.10 Leeds Test to perform a qualitative analysis on a plexiglass phantom simulating in rotation the same thickness parts of the body, with the test in between, exposing the phantom with the two techniques. We asked the radiologists in witch image details were clearer. The same images were analysed from a quantitative viewpoint, by two human observers, determining the Correct Observation Ratio%[2] in order to establish which had the maximum value. Results: We noticed that T2 can entail a higher dose with a maximum of +45% for the elbow and lower dose for foot −43%. In relation to qualitative analysis on X-ray images of patients there was no significant preference of one technique over another. T2 proved to be the best both in qualitative and quantitative analysis for the TO.10 test performed on a phantom and COR% is always higher for T2 compared with T1. Conclusions: Both techniques give good results in terms of dosage and quality. However, it is possible to improve the image quality, without excessive dose increase to the patient by changing and optimising acquisition parameters.